(untitled) (Web of Teachers: Inderscience Research, 2025)
Artificial intelligence is radically changing the world of programming, opening up new opportunities for programmers. With artificial intelligence, programmers can work more efficiently and creatively, solve complex problems and create innovative products. However, artificial intelligence cannot replace programmers, but makes their work easier and more interesting.